Developmental Financial Institutions as Catalysts of Entrepreneurship in Emerging Economies - George, Gerard; Prabhu, Ganesh N. (Academy of Management Review, 2000)
With ongoing privatization efforts in emerging economies, governments have supported developmental financial institutions (DFIs) to spur entrepreneurial activity. The authors use stakeholder theory to suggest that postprivatization stakeholders differ in their preference to seek DFI support. The authors then posit that national developmental priorities influence the DFI's willingness to be involved in the governance of the privatized firm, and they discuss implications of DFI involvement for value creation and entrepreneurship in emerging economies.